2016
DOI: 10.1093/geront/gnw135
|View full text |Cite
|
Sign up to set email alerts
|

Improving Stroke Caregiver Readiness for Transition From Inpatient Rehabilitation to Home

Abstract: The model presented provides a family-centered approach for identifying needs and facilitating caregiver preparation. Given recent focus on improving care coordination, care transitions, and patient-centered care to help improve patient safety and reduce readmissions in this population, this research provides a new approach to enhance these outcomes among stroke survivors with family caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 26 publications
2
95
0
3
Order By: Relevance
“…However, as caregivers are often recruited out of necessity, they may come to the role ill‐equipped, with limited skills and knowledge and feeling underprepared to participate in caregiving. Nurses are ideally placed to be an interface and buffer between caregivers and health services, to evaluate caregiver readiness for the caregiver role and to identify and address specific education and training needs to reduce adverse consequences of caregiving (Lutz et al., ; Schumacher, Stewart, & Archbold, ). Caregivers who report a high level of readiness for caregiving experience lower levels of caregiver strain (Schumacher et al., , ).…”
Section: Practicementioning
confidence: 99%
See 1 more Smart Citation
“…However, as caregivers are often recruited out of necessity, they may come to the role ill‐equipped, with limited skills and knowledge and feeling underprepared to participate in caregiving. Nurses are ideally placed to be an interface and buffer between caregivers and health services, to evaluate caregiver readiness for the caregiver role and to identify and address specific education and training needs to reduce adverse consequences of caregiving (Lutz et al., ; Schumacher, Stewart, & Archbold, ). Caregivers who report a high level of readiness for caregiving experience lower levels of caregiver strain (Schumacher et al., , ).…”
Section: Practicementioning
confidence: 99%
“…Engagement with caregivers should be undertaken with consideration of both commitment and capacity, should be structured through identifying gaps in caregiver and patient needs and strategies to improve caregiver readiness. Caregiver preparation should include activating resources, readying the home environment, providing information and skill training (Lutz et al., ). Consideration should also be given to contextual factors such as pre‐established relationship patterns and an understanding of dyadic care typology (Buck, Kitko, & Hupcey, ).…”
Section: Practicementioning
confidence: 99%
“…5 However, neither is this caregiving role explicitly acknowledged nor is the caregiver's capacity and commitment to providing care assessed. 6 This could result in a mismatch between the expected caregiving responsibilities and the caregiver's ability to fulfil these, potentially leading to adverse consequences for the stroke survivor-caregiver dyad. High reliance on caregivers to assist the stroke survivors in the community implies that caregiver factors like coping or perceived stress can in turn, influence the stroke survivors' outcomes like participation in SCR.…”
Section: Introductionmentioning
confidence: 99%
“…Family caregivers rarely receive adequate preparation for the full extent of caregiving responsibilities (Greenwood et al, 2016;Lutz et al, 2017). They often have numerous and diverse unmet needs across the care continuum (Hafsteindóttir et al, 2011).…”
mentioning
confidence: 99%
“…In addition to screening for physical and psychological health issues, Cameron et al (2016) recommend caregiver assessment to determine specific unmet needs and to integrate knowledge and training into daily activity at each care transition. Lutz et al (2017) also recommend systematic and comprehensive assessment of caregivers prior to discharge to promote successful transitions home. Lutz et al (2011) found that the ability of the caregiver to meet the needs of the stroke survivor influences the success of the family's transition home.…”
mentioning
confidence: 99%